An Analysis Of Multiple Size Region Of Interest In Disparity Mapping For Stereo Vision Application - Hamzah, Rostam Affendi; Hamid, Mohd Saad; Rosly, Hasrul 'Nisham; Hashim, Nik Mohd Zarifie (2011)
This paper presents an analysis of multiple size region of interest in selected area or segment of disparity mapping in application of stereo vision. The mapping is about to deal with the intensities of pixels which allocate the depths of an image and can be extracted to get the distance values. This region is a reference view of the stereo camera and stereo vision baseline is based on horizontal configuration. The block matching technique is briefly described with the performance of its output. The disparity mapping is generated by the algorithm with the reference to the left image coordinate. The algorithm uses Sum of Absolute Differences (SAD) which is developed using Matlab software. The rectification and block matching processes are also briefly described in this paper.